Syndicated Lending: The Role of Relationships for the Retained Share - Alemu Tulu Chala (Lund University, School of Economics and Management, Department of Economics, 2018)
The finance literature offers ambiguous predictions about the impact of lending relationships on the share retained by lead arrangers in syndicated loans. While some literature indicates that lending relationships can help to alleviate post contractual agency conflicts, others imply that relationship lead arrangers may use their information advantage to exploit syndicate participants. Using syndicated loans made to U.S. firms, this article shows that lead arrangers retain a smaller share in lending relationships with firms. This result suggests that the agency-conflict-mitigating feature of a lending relationship outweighs the information-exploitation- facilitating feature. Consistent with the view that reputational concerns mitigate agency conflicts and make relationships less relevant, the impact on the retained share is stronger for non-top-tier and smaller lead arrangers. This article also shows that the effect of lending relationships is concentrated in loan contracts that include covenants.
Keywords: D82; G21; G32; 330; Syndicated lending; Relationships; Retained share